KESULTANAN PANAI PADA MASA PEMERINTAHAN SULTAN GEGAR ALAM TENGKU KELANA PUTERA KABUPATEN LABUHANBATU PROVINSI SUMATERA UTARA TAHUN 1907-1936 - Nirmawan, Muhammad Nanda; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Panai Sultanate is a Malay-style kingdom located on the coast of East Sumatra. The Panai Sultanate was one of the Resident Areas of East Sumatra after the Dutch took control of the Siak Sultanate. The rapid economic development during the reign of Sultan Gegar Alam Tengku Kelana Putra ruled Panai Sultanate in 1907-1936. The purpose of this study was (1) to know the history of the establishment of the Panai Sultanate (2) to know the Sultanate of Panai at the time of Sultan Gegar Alam Tengku Kelana Putera (3) to know the collapse of the Panai Sultanate. This research uses historical methods. The results of this study are the Panai Sultanate which is located in the Sultanate of East Sumatra in the current Labuhanbilik Village. The Panai Sultanate has a blood relationship from the Sultanate of Pinang, namely Batara Sinomba from Pagaruyung. In the time of Sultan Gegar Alam Tengku Kelana Putera there was a shift from a variety of musty covering economic, government and social. The period of setbacks or the collapse of the Panai Sultanate was around 1946 during the Sultan of Tengku Hamlet. The main factor that caused the collapse of the Panai Sultanate was the result of the Social Revolution in the East Sumatra region.Key Words: History, Sultanate Panai